Pharmacological Functions, Synthesis, and Delivery Progress for Collagen as Biodrug and Biomaterial - Nan Zhou; Yu-Da Liu; Yue Zhang; Ting-Wei Gu; Li-Hua Peng (Pharmaceutics, 2023)
Collagen has been widely applied as a functional biomaterial in regulating tissue regeneration and drug delivery by participating in cell proliferation, differentiation, migration, intercellular signal transmission, tissue formation, and blood coagulation. However, traditional extraction of collagen from animals potentially induces immunogenicity and requires complicated material treatment and purification steps. Although semi-synthesis strategies such as utilizing recombinant E. coli or yeast expression systems have been explored as alternative methods, the influence of unwanted by-products, foreign substances, and immature synthetic processes have limited its industrial production and clinical applications. Meanwhile, macromolecule collagen products encounter a bottleneck in delivery and absorption by conventional oral and injection vehicles, which promotes the studies of transdermal and topical delivery strategies and implant methods. This review illustrates the physiological and therapeutic effects, synthesis strategies, and delivery technologies of collagen to provide a reference and outlook for the research and development of collagen as a biodrug and biomaterial.